Strategi Media Relations Dalam Pembentukan Brand Image Universitas Muhammadiyah Jakarta - Sheren Regita Cahyani; Suhaimah .; Salsabilla Narissa Devyanti; Sadiyah El Adawiyah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study analyzes the media relations strategy of Muhammadiyah University Jakarta (UMJ) in shaping its brand image amid fierce competition between private and public universities. Using a descriptive qualitative approach, primary data was obtained through in-depth interviews with the Head of UMJ Public Relations (Sofia Hasna), journalists, and public respondents, supported by secondary data from institutional documents and media reports.Data analysis followed Miles and Huberman's interactive model with triangulation of sources for validity. The results show that UMJ's media relations strategy is coordinated by the University Secretariat Office through the synergy of public relations, multimedia, and protocol, with significant strengthening since 2024/2025. The conventional-digital hybrid approach includes information transparency, strict SEO-based coverage SOPs, situational spokespersons, and personal relationships with top-tier media such as Kompas and Detik.com. This strategy shapes UMJ's brand image as an "impactful, inclusive, and sustainable campus" through consistent news angles on student achievements, lecturer expertise, and Muhammadiyah's contributions, increasing visibility, positive tone, and competitiveness against state universities. Supporting factors include routine monitoring and professional relationships, while obstacles include limited human resources and leadership schedules. The findings enrich Jefkins' (2003) media relations theory and Kotler's brand image indicators, with practical recommendations such as instant communication groups and AI monitoring for similar private universities.